PENGABDIAN MASYARAKAT BERBASIS POTENSI PENDIDIKAN, PELATIHAN, DAN PENYULUHAN DI MI “LITERACY” MIFTAHUL HUDA WAJAK DAN SMK DHARMA WANITA 02 WAJAK - Yanti, Verida; Yazidah, Nok Izatul; Napfiah, Siti; Kartika, Era Dewi (Community Services and Social Work Bulletin, 2024)
Potential-Based Community Service (PMBP) includes education, training, and service which are the Tri Dharma of Higher Education. PMBP activities are important to continue to be carried out by students, the purpose of PMBP is to develop the personality of the students themselves "Personality Development". This PMBP activity was carried out in two different places with different activity programs. The location of the first activity of MI "Literacy" Miftahul Huda Wajak with educational activity programs (reading tutoring and mathematics olympiad), and sports training. The second location is at SMK Dharma Wanita 02 Wajak with a Bullying Counseling activity program. The data collection techniques used in this study are interviews, observations, and documentation. The results obtained in the field of education are in the form of improving reading skills, and practicing the ability to work on mathematics Olympiad problems. In the field of training in the form of providing a basic understanding in sports. In the field of counseling, it is in the form of understanding the dangers and negative impacts of bullying in the school and community environment. This PMBP activity can be able to provide benefits for the schools where PMBP is carried out.